Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content 1. The Prophetic Hadith as evidence for Grammar Co-Prof. Ibrahim Sulaiman Ibrahim Almatroudi 2. Reasoning and its impact on grammatical thought Mr. Majid Mohammad Al-Mozainy 3. Covenant “Lam” and Gender “Lam” in the Holy Quran in light of Al-Baydawi’s interpretation: Linguistic study of selected words Dr. Mkhled Salman Obid Al-Maaitah 4. Semantic Evolution of Terms during COVID: (Prototype of Ministry of Health’s Tweets) Mrs. Latifah Awwadhah Al-Mutairi 5. Extrapolation of the image of the motherhood of the bird in Al-Qama Al-Fahl’s Diwan Lecturer Amani Saud Khishan Al-Qurashi 6. Semiotic connotations in the Arabic novel The Baghdad Morgue, for example Dr. Itidal Salman Iraby, Dr. Sura Saleem Abdel Shaheed 7. Criticism of the Language of the Common People in Al-Misbāh Al-Munīr by Al-Fayoumi (770 AH) Mrs. Maha Abdulaziz Al-Essa